Ultrafast artificial aging of Al–Mg–Si alloys. (February 2016) - Werinos, M.; Antrekowitsch, H.; Kozeschnik, E.; Ebner, T.; Moszner, F.; Löffler, J.F.; Uggowitzer, P.J.; Pogatscher, S.
Abstract: This study investigates the effect of trace Sn additions on the artificial aging of an Al–Mg–Si alloy at unconventionally high temperatures (> 210 °C), where such additions generate both ultrafast aging kinetics and superior peak hardness. The study shows that the effect of Sn is comparable to the influence of natural pre-aging on high temperature artificial aging, and explains this by solute-vacancy interactions, proposing that during artificial aging Sn-vacancy pairs contribute to diffusion and/or Sn retards the annihilation of quenched-in vacancies. Graphical abstract: